KETERKAITAN ENTREPRENEURSHIP DAN EKONOMI KREATIF TERHADAP PERKEMBANGAN POLA PIKIR GENERASI MUDA PADA WIRAUSAHA - MOH. NASIKH (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2019)
The purpose of this study is to determine the relationship between entrepreneurship and creative economy on the thinking patterns of the younger generation in entrepreneurship. The data of this study include: the results of observations, the response of creative economic actors and the response of young people to entrepreneurship. The resource person is determined by using considerations, the selection in accordance with the scope of the study. Data collection is done by observation, interviews, and documentation. The results of the data obtained are then analyzed descriptively. The results showed that there was a link between entrepreneurship and creative economy on the mindset of the younger generation in entrepreneurship. Most of the responses show that entrepreneurship is not a hard choice at present, because with new ideas and innovations and with mature strategies, entrepreneurship is the path to success. However, there are still opinions that state that although there have been examples of success through entrepreneurship, the choice to become an employee still guarantees more survival. The results showed that entrepreneurship with a creative economy that can be done more by young people has an impact on the mindset of the younger generation on entrepreneurship. Entrepreneurship is not a difficult road to success and is no less compared to being a permanent employee.